Exploring the Determinants and Barriers of National Integrity in the Context of Bangladesh - Md. Yeasir Arafat; Md. Mahbubul Alam; Nazmul Hasan Raz; Md. Fairuj Sadaf Opee; Namisa Tabassum; Fahmida (INTERDISIPLIN: Journal of Qualitative and Quantitative Research, 2025)
National integrity is a core aspect of state development, stability and legitimacy. The issue of national integrity becomes especially important in countries such as Bangladesh, where democratic institutions overlap with governance challenges. The article is a qualitative inquiry into some of the key determinants and barriers of national integrity that have been compiled from a broad array of academic and institutional sources. It explores the roles of corruption, institutional trust, rule of law, governance quality, public accountability, civic virtue, and political culture, taking into account recent determinants such as citizen engagement and integrity systems. The paper critically discusses the current discourse and assesses empirical lessons learned on how structural, behavioral, and cultural conditions influence the overall integrity at large (national) scale. By highlighting and analyzing these dynamics, this research illuminates, not just the predicaments and innovations in contemporary Bangladesh, but also wider theories concerning the dynamics of good governance and nation-building. This is the only study employing an integrated approach that combines multi-sectors without primary data to provide an inclusive and well-informed knowledge base, based on confirmed and up-to-date published literature. It fills a critical void in current literature, which has tended to isolate integrity concerns rather